EVALUATION OF THE EFFECTIVENESS OF TECHNOLOGY-BASED LEARNING PROCESSES AND OUTCOMES IN IMPROVING STUDENT COMPETENCE, MOTIVATION, AND ENGAGEMENT: A LITERATURE REVIEW OF DIGITAL ASSESSMENT MODELS IN THE ERA OF EDUCATION 4.0 TRANSFORMATION - Aslan Aslan; Imelda Imelda (CV. ADIBA AISHA AMIRA, 2025)
This study is a literature review that evaluates the effectiveness of technology-based learning processes and outcomes in improving students' competence, motivation, and engagement through digital assessment models in the era of Education 4.0 transformation. This study analyses the relationship between AI-based adaptive assessment, learning analytics, and authentic assessment with student development, supported by learning motivation theory and learning evaluation models. The main findings show a significant positive impact of digital assessment on these three dimensions, with student engagement as the main connecting factor, although it is influenced by teacher readiness and technological infrastructure. This study presents a simple conceptual framework for the development of better digital assessment, along with practical suggestions for educators and policymakers in Indonesia.